The Clinical Legal Education Handbook - Thomas, Linden; Johnson, Nicholas (OBServing Law, 2020)
The Clinical Legal Education Handbook is intended to act as a good practice guide and practical resource for those engaged in the design and delivery of clinical legal education programmes at university law schools. The Handbook is primarily aimed at clinics in England and Wales, but is likely to have content that is of interest to those engaged in clinic in other jurisdictions. The Handbook offers direction on how to establish and run student law clinics and sets out guidance on both the pedagogical and regulatory considerations involved in the delivery of clinical programmes. It also provides an introduction to the existing body of research and scholarship on Clinical Legal Education (CLE). CLE has become an increasingly popular method of legal education in recent years. Despite the popularity of CLE, there is very little guidance available in England and Wales as to how clinics ought to be set up or how clinical programmes might best be delivered. Although the legal regulators have a statutory duty to improve access to justice, it is not always readily apparent how pro bono and CLE fit into a complex regulatory framework. This Handbook aims to address those gaps. The Handbook will be used by staff involved in running law clinics as a practical guide to establishing and running their programmes and can also be used as a teaching resource and recommended text on clinical programmes. It will also be a valuable resource for clinical legal education researchers who wish to engage in regulatory, pedagogic and legal service delivery research in this area.